Investigation and Improvement of Stall Characteristic of High-Lift Configuration without Slats - Zhao Yang; Jie Li; Jing Jin; Heng Zhang; Youxu Jiang (International Journal of Aerospace Engineering)
In order to simplify the manufacturing process or because of the limitation of the propulsion system, business jet, small civil airplane, and turboprop aircraft are always designed without leading-edge slats, which poses a great challenge to the flight safety during takeoff and landing. Focusing on the low-speed stall and poststall conditions, we investigated the aerodynamic characteristics and flow mechanism of high-lift configuration without slats using an improved delayed detached eddy simulation (IDDES) model which is validated by numerical simulations of the Common Research Model (CRM). Based on the analysis of the calculated results, conclusion can be made that the stall behavior of the configurations is directly related to the onset and evaluation of flow separation on the suction side. And through further research, an efficient evaluation method that is capable of qualitatively predicting the stall performance of two-element high-lift configuration by stall angle distribution of wing sections is proposed. By using the evaluation method, together with design rules summarized from the present study, high-lift configuration with mild-stall characteristic can be obtained in the preliminary stage of design.